The middle schools role in the production of social inequalities - Dussel, Ines (Education Policy Analysis Archives, 2014)
This article explores the role of schools in the production and reproduction of social inequalities. It is based upon an empirical research conducted between 2005 and 2007 in twenty-four secondary schools located in the city of Buenos Aires, the surroundings of La Plata, the southern province of Neuquén and the northern province of Salta. It focuses on the findings from interviewing school principals. The analysis runs through four axis: how the inclusion of new social groups, particularly marginalized groups, is being perceived, and how it is changing the functions and operations of secondary schools; how the opposition between “them” (students and their families) and “us” (adults, school system) is played out; how the teaching of communication and expression and the language of rights appear as new formative contents; and how particular horizons for school actions are defined and envisaged. In these four dimensions, the article will seek to identify how social inequalities are being thought in the educational setting, and will inquire whether they are also being produced, and not only reproduced, by the school system.